Kriterien für wirtschaftspolitische Maßnahmen zum Abbau kritischer Importabhängigkeiten - Jürgen Matthes (Wirtschaftsdienst, 2024)
Die Zeitenwende nach dem russischen Angriffskrieg auf die Ukraine und die dadurch verschärfte Debatte über wirtschaftliche Sicherheit, strategische Autonomie und kritische Importabhängigkeiten haben zu Recht dazu geführt, dass Staatseingriffe stärker diskutiert werden. Kritische Importabhängigkeiten sind Abhängigkeiten, bei denen ein Ausbleiben der kritischen Importe etwa aufgrund eines geopolitischen Konflikts wahrscheinlich ist und dies erhebliche volkswirtschaftliche Schäden verursachen würde. Dabei stellt sich die Frage, an welchen Stellen es zu Marktversagen kommt und der Staat intervenieren sollte. – – In this study, an analytical scheme is developed to operationalise the objective of strategic autonomy in a cost-effective way. This is highly relevant as the concept of strategic autonomy is fuzzy and can therefore easily be misinterpreted in a way that would lead to large government subsidies for inefficient purposes in a time of high public debts, low growth and many other public spending needs. The main criteria of the analytical scheme are the degree of critical import dependency on a specific product, the existence of production in the EU and a long-term comparative advantage for this product, as well as the possibility of diversified friend-shoring to secure the supply of this product. Based on a product-specific evaluation of these criteria, it can be determined whether or not government intervention is justified in order to achieve sufficient de-risking of critical import dependencies. This is illustrated using several examples, including raw materials, pharmaceuticals, electric vehicles, batteries for electric vehicles and solar modules. If government intervention is found to be justified, the choice of instrument should be based on the principle that the degree of intervention should be minimised, provided that de-risking objective is sufficiently achieved. Several instruments such as warehousing, incentives for firm-based de-risking, trade barriers and subsidies are discussed. Subsidies in general should be the last resort.
Keywords: F00; O44; L50; 330; Import; Wirtschaftliche Abhängigkeit; Wirtschaftspolitik; Staatliche Einflussnahme; Import; Wirtschaftliche Abhängigkeit; Wirtschaftspolitik; Staatliche Einflussnahme